Estratégias de Blended Learning (ensino híbrido) no ensino de patologia geral em um curso de medicina - Fermozelli, Juliana Abeche (2016)
Currently, in many medical schools, it is noted that learning pathology is poor, mainly due to lack of interest, by students, to knowledge not directly related to professional practice and the lack of teaching resources motivating learning. Blended Learning refers to an education active methodology with different technological resources promoting greater dynamism and integration of those involved. Aim: This research aimed to assess, from the FCMS Medicine student’s point of view at PUC-SP, the motivation and the ability of the contextualization provided by associating Blended Learning to general pathology teaching. Method: Blended Learning sessions were held during supports applied to pathology in the period of October 06 to 31, 2014, on Neoplasms module. Results: In the results, most of the students showed the acceptability to the method, greater motivation and ability to contextualize pathological processes. Discussion: The blended learning can provide students greater contextualization of pathology in medical practice, adding to a meaningful learning